Measurement of the Z boson differential production cross section using its invisible decay mode (Z → νν¯) in proton-proton collisions at √s = 13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen